Яблоки мистера Пибоди: [Сказка] / Мадонна - Мадонна (Эксмо, 2004)
на тит. л. в вып. дан.: Callaway, 2004 Экземпляры: ИН (20071005) / Инвентарный номер: 1065704 / Цена: 127.00 / Сис.шифр: И(Амер) / Авт.знак: М 13 / ГРНТИ: 17 / ББК: 84(4/8)